Pengaruh Literasi Keuangan dan Kecerdasan Intelectual Terhadap Perencanaan Keuangan Dengan Kecerdasan Emosional Sebagai Pemoderasi - Riris Rotua Sitorus; Sihar Tambun; Erna Cahyati (CV. ULIL ALBAB CORP, 2022)
Abstract: This study aimed to examine and analyze the effect of financial literacy and intellectual intelligence on healthy financial planning with emotional intelligence as a moderating variable. The samples in this study were 150 respondents who were students at various universities. The adequacy of the number of respondents was based on the approach used Hair. The data collection technique used simple random sampling by distributing research questionnaires in the form of google and then distributing them to social media. The data processing method in this study used Smart PLS software which is used to test hypotheses. The results of this study indicated that intellectual intelligence had a positive and significant effect on financial planning, emotional intelligence had a positive and significant effect on financial planning, moderating the influence of emotional intelligence on intellectual intelligence on healthy financial planning had proven significant. Emotional intelligence can strengthen the influence of intellectual intelligence on financial planning. The results of this study recommended that students who want to have healthy financial planning, they should be able to consider which needs are more important and understand how to make good financial planning.